Community and ageing : Maintaining quality of life in housing with care settings - Evans, Simon, 1958- (Book collections on Project MUSE., 2009)
This important book investigates changing concepts and experiences of community across the lifecourse and into older age and how they play out in housing with care settings. An overview of how the housing with care sector has developed, both in the UK and internationally, is provided. The book emphasizes the central importance of a sense of community for older people's quality of life and explores the impact of a range of factors including social networks, inclusive activities, diversity and the built environment.